2022
DOI: 10.4103/jisp.jisp_882_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiographic evaluation of advanced-platelet rich fibrin block (A PRF + i PRF + nanohydroxyapatite) compared to nanohydroxyapatite alone in the management of periodontal intrabony defects

Abstract: Background: Several bone grafting formulations have been given clinically acceptable outcomes in treating intrabony defects. Platelet rich fibrin (PRF), an autologous platelet concentrate holds potential to be used for regenerative treatment. The purpose of this study was to evaluate clinical and radiographic outcomes in periodontal intrabony defects treated with advanced-PRF block (A PRF + i PRF + nanohydroxyapatite [nHA]) compared to nHA alone. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Using bone grafts along with PRF can be considered a preventive approach for the loss of labial bone plate, as the thickness of the plate maintains the shape and size of the gingiva which is of prime concern in the esthetic areas. A recent study done using A‐PRF block for regeneration has stated that the use of the block has shown increased osteoblastic activity, with better wound healing and increased tissue remodeling, keeping this notion in mind, A‐PRF block was used in the current study for the management of gingival recession 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using bone grafts along with PRF can be considered a preventive approach for the loss of labial bone plate, as the thickness of the plate maintains the shape and size of the gingiva which is of prime concern in the esthetic areas. A recent study done using A‐PRF block for regeneration has stated that the use of the block has shown increased osteoblastic activity, with better wound healing and increased tissue remodeling, keeping this notion in mind, A‐PRF block was used in the current study for the management of gingival recession 24 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study done using A-PRF block for regeneration has stated that the use of the block has shown increased osteoblastic activity, with better wound healing and increased tissue remodeling, keeping this notion in mind, A-PRF block was used in the current study for the management of gingival recession. 24 Based on that concept in the present study, clinical and radiographic assessment was done in multiple recession defects with A-PRF+ block using the VISTA technique.…”
Section: Discussionmentioning
confidence: 99%
“…Kyyak et al (2021) also revealed that the combination of bovine bone substitute materials with IPRF increases the viability and metabolic activity of human osteoblasts, as well as increases the expression of ALP, BMP-2 at the initial level, and OCN at the final level in vitro [39]. Mallappa et al, (2022) disclosed that the combination of nHA, aPRF, and IPRF materials shows good clinical and radiological results in the treatment of intrabone periodontal defects in humans compared with the single use of nHA [40].…”
Section: Discussionmentioning
confidence: 99%